FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR LULUSAN SARJANA MENJADI AKUNTAN PUBLIK - Yohanes Prabowo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
Purpose of this study was to analyze the factors that influence the selection of career as a public accountant. Factors measured in this study with variable professional recognition, labor market considerations, financial rewards, and intrinsic value of work.Data collected through questionnaires to the students of Trisakti University Faculty of Economics, Faculty of Law, and the Faculty of Art and Design. Used as a sample of 100 respondents. This study has two variables: the independent variable and the dependent variable, where the independent variable is professional recognition, labor market considerations, financial rewards, and intrinsic value of work. While the dependent variable is the selection of career as a public accountant.The analysis showed that in partial professionalpecognition and labourmarketconsiderations significant effect on selection of career as a public accountant. While variable financialreward and intrinsic value works partially no significant effect on selection of career as a public accountant. Kata kunci : Factors career choice as a Public Accountant, public accounting profession